DETECTING OBJECTS MOVING IN SPACE FROM A MOBILE VISION SYSTEM - Spevakov, A. G.; Spevakova, S. V.; Matiushin, I. S. (Radio Electronics, Computer Science, Control, 2019)
Context. In the study, the task of identifying objects moving in space from a mobile system of technical vision is considered. The analysis of the modern methods of dynamic object identification from both stationary and moving platforms is conducted. The need to create a new method for the identification of dynamic objects with a mobile optical-electronic system, which is adaptive to changing observation conditions, is identified. This is a relevant scientific and technical problem. The object of the study is the model of moving object detection from a mobile vision system. Objective. The objective of this article is the analysis of the modern methods of moving object identification and the creation of a new method. The method must allow observation from a mobile vision system and must be able to adapt to changing observation conditions. Method. A method for identifying objects moving in space from a mobile vision system is proposed, which allows to automatically detect moving objects, determine their three-dimensional coordinates with a given accuracy, and adapt to changing observation conditions. This method is based on the developed mathematical model of stereoscopic determination of motion parameters of objects in space, which allows us to increase the detection accuracy. Results. The proposed method is implemented in software. An experiment confirming the adequacy of this mathematical model was conducted. As the result of the experiment, data on the movement of the object and the mobile coordinate system were obtained. Conclusions. The experiments have confirmed the performance of the proposed method and allow us to recommend it when building mobile automatic tracking and identification systems for objects. The method allows automatic isolation of the moving objects, determining their three-dimensional coordinates, and adapting to changing observation conditions. Prospects for further research may be in the creation of hardware tools for the selection of moving objects, allowing to improve the accuracy of the selection.